2020
DOI: 10.1002/cjce.23862
|View full text |Cite
|
Sign up to set email alerts
|

Microporous adsorbent from winemaking waste for the recovery of Mn(VII) in liquid solutions

Abstract: Microporous activated carbon (MAC) was synthesized from winemaking waste and was used to adsorb Mn(VII) from aqueous solutions under various experimental conditions. Moreover, Mn(VII) adsorption on MAC was compared to other adsorbents and an ion-exchange resin, as well as those of other anionic complexes. Langmuir type-1 isotherm best fitted the adsorption process, whereas for all the studied temperatures (30 C-60 C), the experimental data fitted well with the pseudo-second-order kinetic model. The calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…There is also the possibility of producing activated carbon or biochar. Microporous activated carbon obtained from winery waste had a higher capacity to adsorb Mn(VII) than other commercial adsorbents [51] and could be used to successfully remove Pb 2+ from polluted water [52]. Biochar is less expensive to obtain than activated carbon and has a comparable adsorption capacity [43].…”
Section: Obtaining Sorbents From Winemaking Wastementioning
confidence: 99%
“…There is also the possibility of producing activated carbon or biochar. Microporous activated carbon obtained from winery waste had a higher capacity to adsorb Mn(VII) than other commercial adsorbents [51] and could be used to successfully remove Pb 2+ from polluted water [52]. Biochar is less expensive to obtain than activated carbon and has a comparable adsorption capacity [43].…”
Section: Obtaining Sorbents From Winemaking Wastementioning
confidence: 99%
“…Thus, these results indicate that the thickness of the aqueous boundary layer at 1000 min −1 was lowest and leads to a higher adsorption percentage. The decrease in the adsorption of Cr(VI) at higher stirring speeds could be due to the formation of local equilibria, which hinders the adsorption process [31,32]. According to these results, a stirring speed of 1000 min −1 was used in the subsequent experiments.…”
Section: Stirring Speedmentioning
confidence: 99%
“…22 Although there are many treatments for metal ions, few literatures for Mn(VII) are available. [23][24][25] Investigations and studies have shown that the separation of adsorbents accounts for 75% of the overall operating costs. Due to the strong magnetic properties of Fe 3 O 4 , it can be quickly separated from the solution.…”
Section: Introductionmentioning
confidence: 99%
“…This method has high efficiency, low cost as well as large adsorption capacity 22 . Although there are many treatments for metal ions, few literatures for Mn(VII) are available 23–25 …”
Section: Introductionmentioning
confidence: 99%